Feasibility of Responsive Teaching With Mothers and Young Children With Autism in Saudi Arabia. (December 2018) - Alquraini, Turki; Al-Odaib, Ali; Al-Dhalaan, Hesham; Merza, Haniah; Mahoney, Gerald
A randomized controlled trial was conducted to assess the feasibility of Responsive Teaching (RT) with a sample of 28 Saudi Arabian preschool-aged children with diagnoses of autism and their mothers over a 4-month period of time. RT is an early intervention curriculum that attempts to promote children's development by encouraging parents to engage in highly responsive interactions. Subjects were randomly assigned to treatment conditions: the Control group received standard community services; the RT group received weekly RT parent–child sessions in addition to standard services. Consistent with the focus of the intervention, RT mothers made significantly greater increases in Responsiveness and Affect than Control group mothers. There were also significant group differences in pre- and posttreatment measures of children's language and social and fine motor developmental scores. On average, the developmental improvements observed for RT children were 44% greater for social development, 37% greater for language development, and 24% greater for fine motor development than the improvements observed for Control group children. Implications of these findings for providing early intervention services for young children with autism and are discussed.